„Postdokovat po světě“: genderové politiky akademické mobility - Alice Červinková (Gender a Výzkum)
The mobility of scientists that is the subject of this article is part of the broad scale of flows of people, objects, and knowledge in the contemporary world. These flows occur in multiple ways: from relocation and settlement in another country, to everyday pendulating mobility back and forth across boarders. In this article, the author is concerned with academic mobility and particularly mobility tied to long-term post-doctoral fellowships. She sets out to explore the gender dimension of long-term academic mobility and observe how scientists organise their professional and personal lives around movement between academic institutions. She argues that mobility at this stage of the academic trajectory involves the production of new (re)configurations of partnerships, while at the same time the fact of being in a partnership is constitutive for establishing an academic career.